Teknik kursi kosong: Terapi Gestalt untuk mengurangi perasaan marah remaja kepada ayah - Trie Fadilah Hanapi (Procedia : Studi Kasus dan Intervensi Psikologi, 2021)
Individu has problems in life. Inability of the individual to express their feelings can be unﬁnished business problems. In this case subject have an anger on the father that cause a bad interaction with him and juvenile delinquency. Assessment methods were observation, interview, Clinical Anger Scale, Draw a Person, Baum, House Tree Person and the Wechsler Intelligence Scale for Children. It can be said that the subject can not express the feeling to the father, so it becomes an unﬁnished business. The intervention used in this case was Gestalt Therapy with Empty Chair technique. This therapy was able to facilitate the subject in revealing unﬁnished business related problem with the father. The results of the intervention showed that the level of anger of the subject decreases.